Constitutional Design Of Village Head's Term Of Office After Constitutional Court Decision - Chandra SY, Helmi (Badan Pembinaan Hukum Nasional, 2023)
Provisions regarding the tenure of the Village Head have been regulated in Article 39 of the Village Law which explains that the Village Head holds office for 6 (six) years. However, this provision was rejected by the Village Head and requested that the village head's term of office, which was originally 6 (six) years, be extended to 9 (nine) years. Even though there is a Constitutional Court decision Number 42/PUU-XIX/2021 which provides a constitutional interpretation in limiting the term of office for Village Heads. This type of research is legal research using statutory approach methods and conceptual approach methods. The results showed that the design for limiting the term of office for the Village Head in the Constitutional Court decision Number 42/PUU-XIX/2021 was carried out based on democratic principles and the spirit of limitation desired by the 1945 Constitution by following the example of the position of President and Regional Head. The impact of Limiting the Term of Office of the Village Head after the Constitutional Court Decision is to provide a Constitutional interpretation of the term of office for the Village Head, prevent abuse of authority and ensure leadership regeneration.